Oral microbial taxa associated with risk for SARS-CoV-2 infection - Callahan, Nicholas; Hattar, Meryana; Barbour, Thawab; Adami, Guy R.; Kawar, Nadia (Frontiers in Oral Health, 2022)
Hypothesis and objective The oral and digestive tract microbial ecosystem has sparked interest because of its impact on various systemic diseases and conditions. The oral cavity serves not only as a reservoir for many potentially virulent microbiota but also as an important entry point and portal to the human body system. This is especially significant in the transmissibility of the virulent current pandemic virus SARS-CoV-2. The oral and digestive microbiome influences the inflammatory burden and effectiveness of the immune system and serves as a marker of activity of these host processes. The host immune response plays a role in infection susceptibility, including SARS-CoV-2. The purpose of this study is to investigate the role of specific salivary oral microbiome in susceptibility to SARS-CoV-2 infection. Methods and results One hundred six subjects of known medical and dental history who consented to provide saliva samples between January 2017 and December 2019 were included in this study. Sixteen had become COVID-19 positive based on the PCR test by 3/01/2021. A comparison of oral microbiome bacteria taxa profiles based on 16S rRNA sequencing revealed differences between the two groups in this pilot study. Conclusions These bacteria taxa may be markers of increased susceptibility to SARS-CoV-2 infection in the unvaccinated population.